SISTEM MONITORING PENGAIRAN OTOMATIS DENGAN METODE LOGIKA FUZZY - Qirom, Qirom; Niam, Bahrun; Sungkar, Muchamad Sobri (Infotekmesin, 2019)
Rice plant which is a source of food for the people, it needs enough temperature, air humidity and high water for maximum growth. The irrigation system is a major requirement in the field of agriculture, especially for rice plant. Some constraints in conventional irrigation, so they need irrigation system automatically. Some previous studies about automatic irrigation were only used one or two parameters and only used fuzzy or IoT. The method offered in this study uses fuzzy logic using 3 inputs and combines the monitoring system in real time based on IoT. The purpose of this study is to determine the effectiveness of fuzzy logic using three inputs to control the automatic irrigation system byreal time monitoring usingIoT. Data obtained by testing in themorning, afternoon, evening, night and using heat and rain treatment then compared using Matlab calculation. From the tool testing, the average precision of the tool comparison using the calculation is 77.13%.